2011
DOI: 10.1038/onc.2011.345
|View full text |Cite
|
Sign up to set email alerts
|

A novel oncogenic role for the miRNA-506-514 cluster in initiating melanocyte transformation and promoting melanoma growth

Abstract: Malignant melanoma is the most aggressive form of skin cancer and its incidence has doubled in the last two decades. It represents only 4% of skin cancer cases per year, but causes as many as 74% of skin cancer deaths. Early detection of malignant melanoma is associated with survival rates of up to 90%, but later detection (stage III to stage IV) is associated with survival rates of only 10%. Dysregulation of microRNA (miRNA) expression has been linked to tumor development and progression by functioning either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 38 publications
(46 reference statements)
7
108
0
Order By: Relevance
“…[2][3][4][5]13,14 Identification of diagnostic, prognostic, or therapeutic miRNAs has the potential to improve the prognosis for both cutaneous melanoma patients and UM patients. [15][16][17][18] However, to the best of our knowledge, no previous reports on miRNA expression in CM and head and neck MM have been published.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…[2][3][4][5]13,14 Identification of diagnostic, prognostic, or therapeutic miRNAs has the potential to improve the prognosis for both cutaneous melanoma patients and UM patients. [15][16][17][18] However, to the best of our knowledge, no previous reports on miRNA expression in CM and head and neck MM have been published.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we performed an expression analysis of 2578 mature human miRNAs and identified 24 significantly upregulated miRNAs and 1 significantly downregulated miRNA in CM versus normal conjunctiva. Whereas several of these miRNAs have previously been described in cutaneous melanoma, 15,16,18,[21][22][23][24][25][26][27][28][29][30][31] none have been reported previously in UM samples. 17,32,33 It was not possible to collect paired normal tissue for the comparison with CM, which may have limited the number of significant miRNAs identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-506 has been reported to be involved in diverse biological behaviors depending on different target genes. For instance, miR-506 acts as an oncogene in hydroxycamptothecin-resistant human colon cancer cells and melanoma cells [21,22]; however, miR-506 downregulation has been found in ovarian, cervical, lung, and liver cancers [12,14,23], suggesting that miR-506 potentially functions as a tumor suppressor in these cancers. These results suggest that miR-506 might have different roles depending on the cancer type.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased B cell activation, differentiation and survival [64] Low CD 3 + T lymphocytes [53] Increased T cell apoptosis [151] Low IL2 and TH1 responses and thus suppression of T and B-lymphocytes development [53] Oxidative processes -Decreased oxidative damage to mitochondrial DNA [82] -Estrogen protects cells against oxidative stress and acts as a direct antioxidant [82] -High level of anti-oxidant enzymes [86] -High oxidative damage to mitochondrial DNA (4-fold higher compared with women) [82] -Androgens diminish protection against oxidative stress [85] -Decreased number of anti-oxidants and anti-oxidant enzymes [86] -Elevated ROS cellular environment promote tumor metastasis [75,86,87] Sex chromosomes -X chromosome inactivation process: [55,108,109] Decreased tissue X chromosome oncogenes expression [mi-RNAs, cancer/testis antigens (CT-X)] [117][118][119][120][121] Tissue mosaicism in X chromosome associated oncogenes -Lack of Y chromosome associated oncogenes -No X chromosome inactivation process: [55,108,109] Monosomic expression of X chromosome specific oncogenes Increased tissue expression of X chromosome oncogenes -Y chromosome associated oncogene expression [TSPY] [133][134][135][136]139] DNA binding sites to elicit transcriptional regulation of target genes. Studies from androgen receptor knockout mouse models demonstrate that androgens influence the promotion of tumorigenesis in liver and prostate cancer and promote both tumorigenesis and metastasis in bladder, lung, kidney cancers [43], which have sex disparities in outcome favoring women (Table 1, Supplemental Fig.…”
Section: Male Sex Hormonesmentioning
confidence: 99%